U235/U238 izotopik oranının pasif gama-ışını spektroskopisi ile tayini - Özben, Cenap Ş. (Fen Bilimleri Enstitüsü, 1993)
U235/U238 izotopik oranının belirlenmesi gelişen nükleer teknolojiyle önem kazanmıştır. Bu oranın belirlenmesinde en çok kullanılan metodlar, gama spektroskopisi, nötron aktivasyonu, alfa ve kütle spektrometresidir. Bu çalışmada izotopik oranın belirlenmesinde, mevcut imkanlar gözönüne alınarak pasif gama spektroskopisi yön temi seçilmiş ve elde edebildiğimiz bazı numunelerde bu oran belirlenmiştir. U235/U238 izotopik oranının belirlenmesinden önce, gerek dedektör gerekse sayım sisteminin performanslarını belirleyici bir seri ölçümler yapılmıştır. özellikle bunlar arasında dedektörün özelliklerini ve backgroundun etkisini belirleyen hususlar incelenmiştir. Ü235/U238 oranının belirlenmesi için U238 çekirdeklerinin sayısı, U238 'in alfa bozunması sonrasında meydana gelen Th234 'ün beta bozunması sonrasında gönderilen 63 keV ve 93 keV enerjilerdeki dubletler çözülerek örnek içinde ki ü238 çekirdeklerinin sayısı ise bu çekirdeğin alfa bozunmasını takiben gönderilen 186 keV gama ışınının şiddetinden gidilerek bulunmuştur. Ölçülen örneklerde U235/U238 izotopik oranı uranilnitrat ihtiva eden numune için %» 4.3, depleted uran ihtiva eden peletlerde ise %> 0.6 değerleri bulunmuştur.

The determination of u235/U238 isotopic ratio is of great importance in nuclear technolgy, because in many nuclear power reactors enriched fuel is needed. There are some convenient methods to determine this ratio, like thermal neutron activation analysis followed by high resolution gamma-ray, mass, passive gamma-ray, alpha spectrometries and delayed neutron counting. In this work, the passive gamma-ray spectrometry was chosen as the most convenient method which could be made in nuclear physics labratory of Istanbul Technical Uni versity, Department of Physics. This method is based on the measuring of the gamma- rays originate from the decay of u235,U238 and daughters of them. To obtain U235/U238 isotopic ratio, strong gamma-ray at 185.7keV from U235 and doublets at 63 keV and 93 keV of Th234 daughter of U238 decay were used. Activation calculation had been made for doublet in 93 keV (92.35 and 92.78) of Th234 and also for 63.29 peak of 63 doub let. In secular equilibrium the number of U238 atoms can be calculated from the number of Th234 atoms because half life of uranium is much longer than the half life of tho- urium. Samples that we used, were mostly natural uranium and depleted uranium sources. Isotopic ratio determina tion were done for uranylnitrat (U02(N03)2+6H20) from Fluka Inc., Sweden and depleted uranium plates from Reac tor Experiments Inc, U.S.A. and one thick pellet with un known composition. The self absorbtion effect was neg lected for uranylnitrat samples because of it's low den sity and thin thicknesses. Figure 1 shows the spectrum of uranylnitrat sample.
Determination of U235 / U238 isotopic ratio by passive gamma-ray spectrometry
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Keywords: Gama spektroskopisi; Zırhlama; İzotopik oran; Gamma spectroscopy; Shielding; Isotopic ratio